2021
DOI: 10.1101/2021.07.13.452165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards a cumulative science of vocal markers of autism: a cross-linguistic meta-analysis-based investigation of acoustic markers in American and Danish autistic children

Abstract: Acoustic atypicalities in speech production are widely documented in Autism Spectrum Disorder (ASD) and argued to be both a potential factor in atypical social development and potential markers of clinical features. A recent meta-analysis highlighted shortcomings in the field, in particular small sample sizes and study heterogeneity (Fusaroli, Lambrechts, Bang, Bowler, & Gaigg, 2017). We showcase a cumulative yet self-correcting approach to prosody in ASD to overcome these issues. We analyze a cross-lingui… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 72 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…Even though systematic reviews and meta-analyses provide the framework for combining results of several studies, the obtained results should be taken with caution due to several issues including heterogeneity between studies and publication bias 87 . Furthermore, for the topic of the current study, the spoken language of participants and the task that was used for voice elicitation were different extensively between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though systematic reviews and meta-analyses provide the framework for combining results of several studies, the obtained results should be taken with caution due to several issues including heterogeneity between studies and publication bias 87 . Furthermore, for the topic of the current study, the spoken language of participants and the task that was used for voice elicitation were different extensively between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, the outcomes from a systematic review/meta-analysis study can be considered as a starting point in future studies for investigating the effect of potential confounding factors. In this perspective, Fusaroli et al performed a cumulative yet self-correcting approach according to the outcomes of their previous meta-analysis 35 in order to propose guidelines for overcoming the naïve shortcoming of a systematic review/meta-analysis study 87 .…”
Section: Discussionmentioning
confidence: 99%
“…Summary features neglecting the temporal dynamics of vocal productions are likely to neglect relevant aspects of autistic voices. While hand-engineering of temporal acoustic features is certainly an option (Fusaroli et al, 2015), recent developments in time-sensitive algorithms – such as recurrent neural networks dealing with the sequence of acoustic values in time - might also be employed. More radically, in the presence of larger datasets, deep learning algorithms have also been successfully used to automatically infer relevant features from the data.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to mitigate the issue we relied on summary features (median and interquartile range) across each recording and on repeated measures for each participant (2-10 recordings per participant per task). Note that by using summary features of this kind, we are neglecting temporal variation, which are likely to be relevant as markers of autism (Bone et al, 2014; Fusaroli et al, 2015). However, our goal is to assess the generalizability of current ML practices in the field and we leave the identification of better features than those currently used to future work.…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review and meta-analysis (Fusaroli, Lambrechts, Bang, Bowler, & Gaigg, 2017) highlights several potential acoustic contributors to group differences. The meta-analytic findings point to higher pitch, and increased pitch variability, number of pauses and pause duration, although replication attempts show these patterns might be not be generalizable across languages and samples (see, Fusaroli et al 2021). While some studies have found that acoustic differences map onto expert clinician ratings of autism-specific symptoms (McCann et al, 2007; Study 1, Diehl et al 2009), these findings have not always replicated, even within the same lab (Study 2, ibid;Fusaroli et al 2021).…”
mentioning
confidence: 99%